2005
DOI: 10.1007/s11418-005-0013-3
|View full text |Cite
|
Sign up to set email alerts
|

Constituents of Laurus nobilis L. inhibit recombinant human lanosterol synthase

Abstract: Extracts from 37 kinds of foods and foodstuffs were tested for inhibitory activity against recombinant human lanosterol synthase. Among them, extracts from five samples showed significant inhibition. Potent activity (55%) was found in 95% ethanol extract of Laurus nobilis L. Therefore, large-scale methanol extraction of the plant was carried out, and the constituents were separated by partition and fractionation by silica gel chromatography and HPLC. Four flavonoids, kaemperol 3-O-[2¢¢,4¢¢-O-di-E-p-coumaroyla-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Sesquiterpenoids: It was reported in 1971 [35] the isolation from laurel roots of the first sesquiterpene lactone: laurenobiolide (11). Since then, ten more lactones with a germacrane skeleton (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have been isolated from roots [36,37], fruits [38,39] and leaves [37,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Figure 4). Dehydrocostus lactone (22), zaluzanin D (24) and eremanthin (26) were the first lactones isolated from laurel with a guaiane skeleton [38], and santamarine (28) and reynosin (31) the first ones with a eudesmane skeleton [40].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Sesquiterpenoids: It was reported in 1971 [35] the isolation from laurel roots of the first sesquiterpene lactone: laurenobiolide (11). Since then, ten more lactones with a germacrane skeleton (12)(13)(14)(15)(16)(17)(18)(19)(20)(21) have been isolated from roots [36,37], fruits [38,39] and leaves [37,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] (Figure 4). Dehydrocostus lactone (22), zaluzanin D (24) and eremanthin (26) were the first lactones isolated from laurel with a guaiane skeleton [38], and santamarine (28) and reynosin (31) the first ones with a eudesmane skeleton [40].…”
mentioning
confidence: 99%
“…In addition to this group of sesquiterpene lactones, which represent a characteristic group of phytochemicals in L. nobilis, other sesquiterpenoids have been isolated from methanol or chloroform extracts of laurel fruits [38,39] and leaves [41][42][43][44]47,[52][53][54] such as compounds 50-72 ( Figure 4). Eleven of all the sesquiterpenoids found in laurel tree were new natural products (25,27,29,49,50,52,58,(65)(66)(67)72) when isolated.…”
mentioning
confidence: 99%
“…Several studies have screened and prioritized potential LSS inhibitory compounds, including extracts from foods, in different model systems [117][118][119]. These include the experimental compound BIBB-515, which induced 24(S),25 epoxycholesterol and resulted in decreased human rhinovirus replication [120] and sensitized chronic lymphocytic leukemia cells to chemotherapeutics [121].…”
Section: Chemicals That Alter Lanosterol Synthase (Lss) Activitymentioning
confidence: 99%
“…Due to their focus on microorganisms, many of the studies assessing LSS inhibition are solely in vitro analyses. Although many of these studies suggested LSS inhibition, it should be noted that the concentrations of chemical administered were widely variable: from 500 µM eremanthine [119] to screening several compounds at 20-50 µM [118] and 0.25-0.5 µM diacylglycerols [125].…”
Section: Chemicals That Alter Lanosterol Synthase (Lss) Activitymentioning
confidence: 99%
“…We found its potent inhibitory activity against lanosterol synthase and isolated its constituents to obtain four flavonols and six sesquiterpenes. Of these, eight compounds had moderate inhibitory activity, and eremanthine, a sesquiterpene, was the most potent [ 49 ]. In addition, we screened Brazilian herbs for inhibitory activity against lanosterol synthase, and Paffia paniculata , Trichilia catigua , and Maytenus ilicifolia showed the most potent activity [ 50 ].…”
Section: Regulatory Science Of Foodsmentioning
confidence: 99%